Multifactor Authentication for Hospital Inventory access in Virtual Private Cloud - deep, Gaurav; Kaur, Paramroop; Mohana, Rajni (International Journal of Engineering and Technology, 2018)
In recent times, cloud computing has influenced every sector of life, from managing user database online on the cloud to access it on the cloud makes it more flexible to use. Cloud computing has its own security issues like privacy, integrity, confidentiality and authentication. In order to access data on the cloud Authentication majorly plays a very important role. This paper presents a secure multifactor authentication that can be used for Hospital Inventory access in Virtual Private Cloud. Virtual Private cloud is having the benefit of localization as all the data of cloud are accessible within the organization. To secure Hospital Inventory access in Virtual Private Cloud this paper proposes multifactor authentication technique using Biometric, MAC address via payload .The proposed a multifactor authentication protocol which is also validated by using a validation tool Scyther. The outcomes indicate that the proposed multifactor authentication is a robust technique.Â